Transformation, Internalization, and Media Socialization of Core Values for State Civil Apparatus (ASN) - Syaputra, Hendry; Abdullah, Aceng; Sjafirah, Nuryah Asri (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
In 2021, the Ministry of PANRB launched the Core Values and Employer Branding for the State Civil Apparatus (ASN) in Indonesia, known as